Strategic National Plan 2023-2027: Opportunities or constraints for sustainable agriculture in Romania? - Lorena Florentina Chițea (Agrarian Economy and Rural Development - Trends and Challenges. International Symposium. 14th Edition, 2023)
The present work aims to make a synthesis of the specialized literature and European and national policies and strategies regarding the promotion of sustainable agriculture. In this way, an overview is achieved, in which synergies and common objectives can be noticed between various European policies and strategies that are based on the European Green Deal, these being the "Farm to Fork" Strategy, the Biodiversity Strategy, the EU Soil Strategy for 2030, the LongTerm Vision for the EU's Rural Areas. The four strategies are correlated with the three pillars of sustainability: Environment, Economy, Society. In the face of the new European policies and strategies that promote sustainable agricultural practices with beneficial environmental and health effects on the long term, which can contribute to reducing the effects of climate change, Romania, through the National Strategic Plan 2023-2027, has ambitious targets to achieve, which will represent a great challenge in the next period.
Keywords: Q01; Q18; 330; sustainable development; sustainable agriculture; agricultural policies